Factors influencing self-efficacy beliefs of interdisciplinary science teaching – the role of teaching experience, science subjects studied, and desire to teach interdisciplinary science - von Knebel, Kevin; Schroeder, Sascha; Bögeholz, Susanne (Frontiers in Education, 2023)
Teacher education for interdisciplinary science teaching at secondary schools shows shortcomings in several countries. One of these countries is Germany. Germany provides teacher education studies for secondary education in biology, chemistry, and physics. This discipline-specific single science subject teacher education results in partly out-of-field teaching of secondary teachers regarding interdisciplinary science. Thus, interdisciplinary science teaching is a new and difficult challenge for (prospective) teachers in Germany. Self-efficacy beliefs refer to the belief in the own abilities to tackle new and difficult challenges, such as interdisciplinary science teaching. Empirical research on self-efficacy beliefs of interdisciplinary science teaching (SElf-ST) is important to foster SElf-ST, for example, in teacher education. Up to now, empirical research on influencing factors on SElf-ST takes mainly primary education into account. Empirical evidence for influencing factors regarding secondary science education is still needed because of the context-specificity of self-efficacy beliefs. Thus, this paper investigates factors possibly influencing SElf-ST in secondary education: teaching experience, number and type of science subjects studied and desire to teach interdisciplinary science. We conducted a cross-sectional questionnaire study with German pre-service, trainee, and in-service biology, chemistry, and physics teachers (n = 589) on SElf-ST. In-service teachers had the highest beliefs in nearly all SElf-ST scales. Hardly any difference occurred between trainee teachers and pre-service teachers. Our study provides empirical support that in addition to teaching experience, the number of studied science subjects, and the desire to teach interdisciplinary science are factors that influence SElf-ST not only in primary education but also in secondary education. The novel examination of the so far unknown influence of studying biology, chemistry, or physics on the SElf-ST reveals an impact of any subject but in different ways. The effect of studying chemistry on the science-teaching-specific SElf-ST stands out. In sum, our results reveal possibilities in the context of, e.g., organizing teacher education to promote (prospective) teachers’ SElf-ST in secondary education.